Access to medicines in Burkina Faso under the agreement on trade-related aspects of intellectual property rights and the Economic Partnership Agreement - Kabre, Rimdolmsom Jonathan (University of Pretoria, 2023)
Mini Dissertation (LLM (International Trade and Investment Law))--University of Pretoria, 2023.